Genetic Counselling, Testing, and Management of Hereditary Breast and Ovarian Cancer Syndrome in India: Updated Expert Consensus Recommendations from Indian Society of Medical and Pediatric Oncology - Malhotra, Hemant; Pramanik, Raja; Srinivas, Sujay; Kotwal, Pradyna; Mehra, Nikita; Gupta, Sudeep; Rajkumar, Thangarajan; Sarin, Rajiv; Kanakasetty, Govind Babu; Bapna, Ajay; Smruti, B. K.; Sekhon, Rupinder; Basade, Maheboob; Gupta, Sabhayata; Maheshwari, Amita; Somashekhar, S. P.; Kadayaprath, Geeta; Krishnamurthy, Arvind; Punia, Anushree; Suryavanshi, Moushumi; Gupta, Rekha; Verma, Amit; Kulkarni, Padmaj; Parikh, Purvish (Indian Journal of Medical and Paediatric Oncology, 2025)
Introduction Hereditary breast and ovarian cancer (HBOC) is driven by mutations in BRCA1/2 and related genes. Their understanding is vital to appropriate management of such patients and at-risk families, including counselling and genetic testing. Several important recent advances have made it necessary to revise the previous recommendations we made for India in 2020.Materials and Methods This consensus document was developed with the authors as key experts in the field. Published evidence, real-world data, and expert interpretation were used by a modified Delphi method to finalize these recommendations.Results Detailed description and process for identifying patients at risk, doing their counselling, selecting the right molecular test, interpreting the results, and determining the optimal mode of action to attenuate risk of HOBC or its recurrence have been provided in a clear and lucid manner. Differences between germline and somatic mutations are described. Information from publicly available databases was used to fine-tune the guidelines—as more information had becomes available since the time of writing the first guidelines. Risk of various cancer types and corresponding risk reduction strategies have been explained.Conclusion Community oncologists in India, SAARC region, and other low- and middle-income countries should use these guidelines in their clinical practice to optimize genetic counselling, molecular testing, and management of patients with HBOC.
Keywords: hereditary cancer; therapy; driver mutations; guidelines